Hybrid GMR/IR probe to reduce the effects of lift-off - Faraj, Moneer A.; Fahmi, Samsuri; Abdalla, Ahmed N.; Rifai, Damhuji; Kharudin, Ali; Al-Douri, Y. (Sage Publications Ltd, 2019)
Eddy current testing technique is being utilized in engineering, such as in nuclear steam pipe, aircraft and gas/oil pipeline, due to its sensitivity to small cracks and subsurface defects, immediate results, environmental friendliness, and use in examining complex sizes and shapes of substances. However, the lift-off noise due to irregular inspected materials surface, varying coating thicknesses, or movement of transducers extremely limits the implementation of eddy current testing in a non-disastrous testing which impacts the measure of defect depth on the conductive material. In this paper, a study on hybrid giant magneto-resistance/infrared probe is proposed to minimize the influence of lift-off for detecting the depth defect. The giant magneto-resistance reads the magnetic field which reflects any defect inside the pipeline, and infrared sensors read the movement of each giant magneto-resistance inside the pipeline. The error compensation technique depends on Mamdani fuzzy which examines the interaction that exists between the peak value of giant magneto-resistance and the infrared sensor signal. The eddy current testing inspection system includes details of the giant magneto-resistance–eddy current probe design and instrumentation of the error compensation technique. The measurement method is based on alternating current supply with 30 kHz frequency to ensure that the crack signals are clearly displayed. The proposed method is verified experimentally, and the result shows that the impact of lift-off noise is highly reduced in the eddy current testing technique and enhances the sensor accuracy. The depth defect error caused by 1 mm lift-off is reduced to 7.20%.